2017
DOI: 10.1507/endocrj.ej16-0534
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-stimulating hormone stimulation downregulates autophagy and promotes apoptosis in chondrocytes

Abstract: OSTEOARTHRITIS (OA) is the most common form of arthritis that affects about 3.8 % of people in the world [1]. OA results from the breakdown of articular cartilage, which is an avascular tissue with limited regenerative ability. As the only cell type in cartilage, the chondrocyte death / survival has a key role in cartilage maintenance and functionality. Apoptosis in chondrocytes has been detected in articular cartilage derived from OA patients [2], suggesting a crucial role for chondrocyte apoptosis in the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Specifically, based on cDNA array hybridization, Brokken et al revealed that most of the genes regulated by TSH are related to cell apoptosis [ 42 ]. Further, Xin et al reported that TSH stimulation upregulates Bax expression and downregulates Bcl2 expression, thus disrupts the balance between Bax and Bcl2, while promoting chondrocyte apoptosis [ 43 ]. It has also been reported that TSHR upregulation promotes the apoptosis of thyroid cancer cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, based on cDNA array hybridization, Brokken et al revealed that most of the genes regulated by TSH are related to cell apoptosis [ 42 ]. Further, Xin et al reported that TSH stimulation upregulates Bax expression and downregulates Bcl2 expression, thus disrupts the balance between Bax and Bcl2, while promoting chondrocyte apoptosis [ 43 ]. It has also been reported that TSHR upregulation promotes the apoptosis of thyroid cancer cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although p62 expression is reported to be up-regulated at the transcription levels in certain conditions [ 37-39 ], our results indicate that TSH decreases the degradation rate of p62, meaning that TSH action is at posttranslational rather than transcriptional levels. As mentioned in the Introduction, TSH is reported to suppress autophagy (as demonstrated by reduced LC3-II and increased p62 levels) in chondrocytes by inhibiting phosphorylation of AMPK [ 14 ]. The detailed mechanisms for the differences in our data and theirs are at present unknown, but TSH action on autophagy appears to be cellular context dependent.…”
Section: Discussionmentioning
confidence: 99%
“…However, regulation of autophagy in thyrocytes by hormones such as TSH and thyroid hormone (TH) has not been studied. We found 1 paper reporting TSH suppression of autophagy in chondrocytes [ 14 ], and several papers showing TH enhancement of autophagy in different types of mammalian cells, such as liver, muscle, and fat cells [ 15-17 ]. Hormonal regulation of autophagy has also been recently examined in various organs, such as Sertoli cells by testosterone, liver by growth hormone, and skeletal muscle by insulin (ref.…”
mentioning
confidence: 99%
“…(28) In consistence with the present result, Xin et al mentioned that TSH elevated with the hypothyroidism considered an apoptotic factor resulting in significant increase in serum 8-hydroxyguanosine and caspase-3. (29) The increasing in cortisol and stress oxidative markers in hypothyroid rats caused an elevation of reverse T 3 (rT3), which was interfered with beneficial activity of normal T 3 . Ginseng by its adaptogenic capability action could destroy the (rT3) and restore the cellular homeostasis.…”
Section: Discussionmentioning
confidence: 99%